Recent developments in the genetics of attention‐deficit hyperactivity disorder. Issue 9 (1st August 2018) - Grimm, Oliver; Kittel‐Schneider, Sarah; Reif, Andreas
Abstract : Attention‐deficit hyperactivity disorder (ADHD) is a developmental psychiatric disorder that affects children and adults. ADHD is one of the psychiatric disorders with the strongest genetic basis according to familial, twin, and single nucleotide polymorphisms (SNP)‐based epidemiological studies. In this review, we provide an update of recent insights into the genetic basis of ADHD. We discuss recent progress from genome‐wide association studies (GWAS) looking at common variants as well as rare copy number variations. New analysis of gene groups, so‐called functional ontologies, provide some insight into the gene networks afflicted, pointing to the role of neurodevelopmentally expressed gene networks. Bioinformatic methods, such as functional enrichment analysis and protein–protein network analysis, are used to highlight biological processes of likely relevance to the etiology of ADHD. Additionally, copy number variations seem to map on important pathways implicated in synaptic signaling and neurodevelopment. While some candidate gene associations of, for example, neurotransmitter receptors and signaling, have been replicated, they do not seem to explain significant variance in recent GWAS. We discuss insights from recent case–control SNP–GWAS that have presented the first whole‐genome significant SNP in ADHD.